Why Does Copyright Law Meet Criticism in Society? The Importance of the Public Domain - Vohid, Alimardanova Iroda (Researchparks Publishing, 2024)
This article is about a well-stocked public domain and equitable access to copyright-protected content to foster innovation and the creation of new works. It is a common misconception that stronger intellectual property rights promote economic progress, whereas copyright exceptions need to be somewhat conceded for socially motivated reasons. This is a false dichotomy. For the sake of research and development, teaching, and software or hardware interoperability, many companies need access to copyrighted materials. A lack of appropriate access can impede economic expansion.